Analisis Rasio Profitabilitas Untuk Menilai Kinerja Keuangan (Studi Kasus Pada Perusahaan Kosmetik Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2019) - Astuti, Yuni Tri; Febriyanto, Febriyanto (Jurnal Manajemen DIVERSIFIKASI, 2021)
The assessment of financial performance can be done by management by analyzing the financial statement. The financial statements which has been is the balance sheet and profit and loss statement in 2016 until 2019. One analysis that can be used to determine the company's financial condition is financial ratio analysis. The purpose of this study was to determine how the financial performance of the cosmetics sub-sector in terms of profitability ratios based on the company's financial statements. The data analysis method used is descriptive analysis. Research data and information were obtained from the Indonesia Stock Exchange. From the calculation of the average profitability ratio on the net profit margin, the condition of the company's financial performance is not good and the return on assets, return on equity shows that the condition of the company is in good condition. From the results of the financial ratio analysis, it can be seen that PT Unilever Tbk has a better financial performance compared to the other three cosmetic companies.